Relation between Pulse Pressure, Hypertensive Retinopathy, and Other Cardiovascular Risk Factors among Hypertensive Patients in Cameroon - Hamadou, Ba; Ndongo Amougou, Sylvie; Sadou, Hamadou; Kamdem, Félicité; Nganou, Chris Nadège; Kuate-Mfeukeu, Liliane; Boombhi, Jerôme; Menanga, Alain Patrick; Kingue, Samuel (HEALTH SCIENCES AND DISEASE, 2018)
ABSTRACT Introduction. There are few studies on the prevalence of hypertensive retinopathy and the specific role of pulse pressure in the occurrence of cardiovascular complications in general and hypertensive retinopathy in particular in Cameroon. The aim of this study was to investigate the relationship between pulse pressure, hypertensive retinopathy and cardiovascular risk in a group of hypertensive patients in Cameroon. Methods. We carried out an analytic cross-sectional study from October 2016 to May 2017 in three hospitals in Garoua (Cameroon). We included all known hypertensive patients aged over 18 years consulting in selected hospitals, who provided their written inform consent. Patients with concomitant diabetes or presenting a contraindication to eye dilation were excluded. Each patient underwent an interview using a standard questionnaire, physical examination with including measurement of blood pressure and anthropometric parameters. A complete eye examination was carried out in search of hypertensive retinopathy. Results. We included 130 participants (65.4% females) with a mean age of 53.18 ± 10.7 years, and a mean duration of hypertension of 5.9 years. 79.2% of participants were on pharmacological treatment –mainly calcium inhibitors (50.3%) and thiazides diuretics (17.2%). 23.9% already presented with target organ lesions. Hypertensive retinopathy was seen in 16% of patients, and was associated with male sex, target organ damage, and age ≥65 years. Pulse pressure correlated with age, mean arterial blood pressure and systolic blood pressure. However, we found no association between pulse pressure and hypertensive retinopathy. Conclusion: Hypertensive retinopathy is frequent in Cameroonian hypertensive patients, and is associated with other target organ lesions but not with pulse pressure. RÉSUMÉ Introduction. Au Cameroun, il existe peu de données sur la prévalence de la rétinopathie hypertensive et le rôle du niveau de pression pulsée dans la survenue des complications cardio-vasculaire. L’objectif de ce travail était d’étudier la relation entre une élévation de la pression pulsée et la rétinopathie hypertensive chez un groupe de patients hypertendus au Cameroun. Méthodes. Il s’agissait d’une étude transversale à visée descriptive et analytique, qui s’est déroulée sur une durée de 08 mois allant d’octobre 2016 à Juin 2017 dans trois hôpitaux de la ville de Garoua. Nous avons recruté les patients hypertendus âgés de 18 ans révolus consentants, venus consulter dans ces formations hospitalières. Les patients diabétiques ou avec une contre-indication à la réalisation d’un fond d’œil ont été exclus. Les données socio-démographiques, les antécédents personnels et familiaux du malade ont été collectés. Un examen physique complet avec une prise des paramètres anthropométriques a été réalisé au premier contact. Par la suite un fond d’œil a été réalisé à la recherche de rétinopathie hypertensive. Résultats. Nous avons recruté 130 patients (65,4% des femmes), âgés de 53 ± 10,7 ans, avec une durée moyenne de l’hypertension de 5,9 ans. 79,2% des patients étaient sous traitement antihypertenseur dont 50,29% sous inhibiteurs calciques et 17,2% sous diurétiques thiazidiques. 23,9% des patients sous traitement antihypertenseur ont présenté une atteinte d’organe cible de l’HTA. La prévalence de la rétinopathie hypertensive dans la population des hypertendus était de 16% et était associée à l’âge avancé (>65 ans), au sexe masculin et à l’existence d’une lésion d’organe cible. La pression pulsée était statistiquement corrélée à l’âge, à la pression artérielle moyenne et à la pression artérielle systolique. Il n’y avait pas d’association entre la pression pulsée et la rétinopathie hypertensive. Conclusion. La rétinopathie hypertensive est fréquente dans notre contexte bien qu’elle ne soit pas associée à la pression pulsée. Les facteurs associés à sa survenue sont : l’âge avancé (> 65 ans), le sexe masculin et l’existence d’autres lésions d’organes cibles de l’hypertension.